Dampak Anggaran, Kesulitan Geografis, dan Rumah Tangga Desa terhadap Status Desa di Provinsi Riau: The Impact of Budget, Geographic Difficulty, and Village Households on Village Status in Riau Province - Bakti Kharisma; Werry Darta Taifur; Fajri Muharja (P4W LPPM IPB, 2021)
Enactment of the Village Law brings enthusiasm to the rural development paradigm. One of the main outputs of the government planning document is the increase of priority development in rural areas and villages. This is implemented by increasing the source of village income budget through the village fund program. This study aims to analyze the impact of village budgets and geographic difficulties, and village households on village status in Riau Province. Multiple linear regression model was used to analyze the impact of Village Fund allocation, Village Fund, Geographical Difficulty Index, and number of households in 2018 on the achievements of the Developing Village Index in 2019. Research results show that Village Fund allocation budget and the number of households have positive impacts on the Developing Village Index (Indeks Desa Membangun). in Riau Province. Meanwhile, increase in Village Fund budget and Geographical Difficulty Index have negative impacts on the Developing Village Index in Riau Province.